2020
DOI: 10.1021/acs.est.0c01840
|View full text |Cite
|
Sign up to set email alerts
|

Novel Syntrophic Isovalerate-Degrading Bacteria and Their Energetic Cooperation with Methanogens in Methanogenic Chemostats

Abstract: Isovalerate is an important intermediate in anaerobic degradation of proteins/amino acids. Little is known about how this compound is degraded due to challenges in cultivation and characterization of isovalerate-degrading bacteria, which are thought to symbiotically depend on methanogenic archaea. In this study, we successfully enriched novel syntrophic isovalerate degraders (uncultivated Clostridiales and Syntrophaceae members) through operation of mesophilic and thermophilic isovalerate-fed anaerobic reactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Moreover, Methanosarcina higher expressed the genes involved in CO2-reducing pathway in ATL compared to PTL and VTL (Tables S3 and S4, [28,30]). These results implied that Methanosarcina played a multi-trophic functional role in thermophilic chemostats.…”
Section: Energy-conserving Metabolisms In Methanogensmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Methanosarcina higher expressed the genes involved in CO2-reducing pathway in ATL compared to PTL and VTL (Tables S3 and S4, [28,30]). These results implied that Methanosarcina played a multi-trophic functional role in thermophilic chemostats.…”
Section: Energy-conserving Metabolisms In Methanogensmentioning
confidence: 99%
“…The completeness was calculated based on the number of expected marker genes present in MAGs, while the contamination based on the number of expected marker genes present in multiple copies. Genes were annotated using Prokka [81] and manual curation was performed as described previously [30]. Phylogenomic trees were built with PhyloPhlAn v0.99 ("-u" option) [82], and the tree was edited using iTOL [83].…”
Section: Operation Of Thermophilic Anaerobic Chemostatsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with other communities, the available energy is relatively limited in the AMC system and thus plays fundamental roles in driving the evolution of the community members involved ( Lyu et al, 2018 ), as well as being associated with the metabolic interactions among these members ( Jackson and McInerney, 2002 ; Nobu et al, 2020 ). In our previous works, we enriched four AMCs in thermophilic methanogenic chemostats supplemented with acetate, propionate, butyrate, or isovalerate as sole carbon source (accordingly, the four chemostats were simplified as ATL, PTL, BTL, and VTL thereafter) ( Zheng et al, 2019 ; Chen et al, 2020a , b ). Because AA is one type of important public functions that have been reported in many microbial communities [e.g., in ocean ( Barbara and Mitchell, 2003 ) and in human gut ( Perna et al, 2019 ), as well as other AMC systems ( Embree et al, 2015 ; Hubalek et al, 2017 )], we analyzed the abilities of AA synthesis of syntrophic acetate-oxidizing bacteria (SAOBs) involved in our enriched AMCs and found that AA synthesis ability was deficient in most of the SAOBs in our AMCs ( Zeng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%